Predictive risk factors before the onset of familial rheumatoid arthritis: the Tatarstan cohort study - Arleevskaya, Marina I.; Larionova, Regina V.; Shagimardanova, Elena I.; Gogoleva, Natalia E.; Kravtsova, Olga A.; Novikov, Andrej A.; Kazarian, Gevorg G.; Carlé, Caroline; Renaudineau, Yves (Frontiers in Medicine, 2023)
Background: A familial history of rheumatoid arthritis (RA) predisposes an individual for developing RA. This study aimed at investigating factors associated with this conversion from the Tatarstan cohort.Methods: 144 individuals, referred to as pre-RA and at risk for familial RA, were selected 2 years (range: 2 to 21 years) before conversion to RA and compared to non-converted 328 first degree relatives (FDR) from RA as assessed after ≥ 2 years follow-up, and 355 healthy controls (HC). Preclinical parameters, and socio-demographic/individual/HLA genetic factors were analyzed when data were available at the time of enrolment.Results: As compared to FDR and HC groups, pre-RA individuals were characterized before conversion to RA by the presence of arthralgia, severe morning symptoms, a lower educational level, and rural location. An association with the HLA-DRB1 SE risk factor was also retrieved with symmetrical arthralgia and passive smoking. On the contrary, alcohol consumption and childless in women were protective and associated with the HLA-DRB1*07:01 locus.Conclusion: Before RA onset, a combination of individual and genetic factors characterized those who are at risk of progressing to RA among those with familial RA relatives.